2019
DOI: 10.1002/pds.4796
|View full text |Cite
|
Sign up to set email alerts
|

Nature and frequency of dosing instructions on prescription labels in primary care

Abstract: Purpose To investigate the nature and frequency of dosing instructions and auxiliary labels on prescription labels in primary care. Methods A retrospective analysis of data on prescription labels of dispensed drugs extracted from the pharmacy information system of community pharmacies in the Netherlands. Dosing instructions were categorized into four types. Results Data were extracted from 123 community pharmacies. All drugs dispensed for a random sample of 10% of patients were selected. In the sample of 938 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Moreover, research of Borgsteede and Heringa (2019) showed a substantial proportion of Dutch prescription label instructions was too complex, and could be optimized by rephrasing them. In this study, we collected data about the comprehensibility of dosage instructions, auxiliary label warnings or advices, and how they are interpreted by patients with limited and adequate health literacy using a mixed methods approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, research of Borgsteede and Heringa (2019) showed a substantial proportion of Dutch prescription label instructions was too complex, and could be optimized by rephrasing them. In this study, we collected data about the comprehensibility of dosage instructions, auxiliary label warnings or advices, and how they are interpreted by patients with limited and adequate health literacy using a mixed methods approach.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research of Borgsteede and Heringa (2019) showed a substantial proportion of Dutch prescription label instructions was too complex, and could be optimized by rephrasing them. For example, of the 100 most frequently used dosage instructions, 23.8% were instructions for multiple times a day use without specifying the time of day (e.g., “1 tablet 2 times a day”), and 13% contained general instructions or instructions to “take as needed.” Arguably, as the instructions were about one-third of the total, the potential improvement on a population level is significant.…”
Section: Introductionmentioning
confidence: 99%
“…The content and format of dispensing labels provided by pharmacies varies between and within jurisdictions. [11][12][13] To standardise the content and format of dispensing labels and to improve the comprehension of dosage instructions by patients, the concept of patient-centred labels (PCL) has been introduced. 14 15 PCL are designed to provide information in a more reliable way than standard labels.…”
Section: Open Accessmentioning
confidence: 99%
“…As such, numerous studies related to this topic have been published ( Maghroudi et al, 2021 ). Studies have focused on factors such as, complexity of dosing instructions particularly in relation to patient health literacy ( Beckman et al, 2005 ; Shrank et al, 2007 ; European Commission, 2009 ; Bailey et al, 2012 ; Emmerton et al, 2012 ; Koster et al, 2014 ; Patel et al, 2018 ), requirements concerning content an comprehensibility of the text ( Raynor and Bryant, 2013 ; Pires et al, 2016 ; Yuan et al, 2019 ), precision of writing dosing instructions ( Borgsteede and Heringa, 2019 ), and the use of icons, graphics and pictograms ( Kheir et al, 2014 ; van Beusekom et al, 2017 ). As a result, guidelines have been drawn up with standards on how information should be presented on the PDL (i.e.…”
Section: Introductionmentioning
confidence: 99%